Automatic speed controller for fan and coolers / Kausar Mohd Zain and Siti Farah Hashim - Mohd Zain, Kausar; Hashim, Siti Farah (2002)
Our project , a speed controller for fan and cooler is a system that control the temperature when it is low or high condition. The operation is in automatic function. The circuit is combination between decade divider / counter and IC timer. When output Q4 is goes low and Q5 goes high relay R2 is switched off and relay RL 4 activated the fan now runs at low speed in the motor used in certain cooler there are separate speeds. Thus , initially the fan and cooler needs to be run at full speeds. As time passes by, one has set up again to adjust the speed of the fan and cooler. Here, no need to adjust it because it will switch off by itself after operate 8 hours.